Going Global : Expanding Offshore Wind to Emerging Markets - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2019)
For many years, offshore wind was the expensive cousin of onshore wind with generation costs in the range of $150 to $200 per megawatt hour (MWh). This changed dramatically between 2016 and 2017 when a series of competitive tenders in Europe witnessed strike prices fall below $100/MWh, culminating in projects that bid into merchant markets with no subsidy at all. Prices have continued to drop thanks to technological improvements, economies of scale, maturation of supply chains, better procurement strategies, and the efforts of large and sophisticated project developers, including several from the utility and oil and gas sectors. However, to date the offshore wind industry has remained largely confined to Europe and China. As prices continue to drop, offshore wind is increasingly gaining traction in emerging markets. Projections suggest that offshore wind will add between 7 to 11 gigawatts (GW) per year from 2019 to 2024, reaching between 15 to 21 GW/year from 2025 to 2030. While much of the growth is expected in Europe, China, and new Organization for Economic Co-operation and Development (OECD) markets including Japan, South Korea, and the United States, there is ample potential for developing countries to ride on this momentum and ramp up their local offshore markets. This report presents eight case studies on the technical potential for offshore wind in Brazil, India, Morocco, the Philippines, South Africa, Sri Lanka, Turkey, and Vietnam (here, technical potential is calculated on the basis of wind speed and water depth). Considering offshore areas within 200 kilometers (km) of the coast, 3 these eight countries have a total technical potential of approximately 3.1 terawatts, including 1,016 GW of fixed capacity and 2,066 GW of floating capacity. UPDATE (May 2020): Since publication of this report the World Bank has published 56 country and regional maps, including updated versions of the maps available in this report. The maps can be accessed via the ESMAP website: https://esmap.org/node/197070.